Diaphragmatic Hernia with Atypical Presentation - A Case Series (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Congenital Diaphragmatic Hernia is one of the most challenging diagnosis faced by pediatric surgeons. From the time of its first anatomic description more than 300 years ago, CDH has carried a high mortality rate. We aimed to review patients who presented with hernia of diaphragm during the last six months. In this retrospective study, the medical records of three patients treated for diaphragmatic hernias who were admitted to Rajshahi Medical College Hospital between July 2012 and December 2012 were analyzed. Three patients with age of 45 days to 7 years were included in the study. Male to female ratio was 1:2. All patients had left-sided diaphragmatic hernia. Chest X-ray was obtained from all patients which was diagnostic. One patient needed thoracotomy incision. No patient required mesh repair. The mean hospitalization time was 14 days. There was no postoperative death. Diaphragmatic hernia is an uncommon and challenging situation for the surgeon. Prompt diagnosis and treatment prevent serious morbidity and mortality associated with complications such as gangrene and perforation of herniated organ. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21050 J Bangladesh Coll Phys Surg 2014; 32: 45-50